Tripartite symbiosis of Sophora tomentosa, rhizobia and arbuscular mycorhizal fungi - Toma,Maíra Akemi (2017)
ABSTRACT Sophora tomentosa is a pantropical legume species with potential for recovery of areas degraded by salinization, and for stabilization of sand dunes. However, few studies on this species have been carried out, and none regarding its symbiotic relationship with beneficial soil microorganisms. Therefore, this study aimed to evaluate the diversity of nitrogen-fixing bacteria isolated from nodules of Sophora tomentosa, and to analyze the occurrence of colonization of arbuscular mycorrhizal fungi on the roots of this legume in seafront soil. Thus, seeds, root nodules, and soil from the rhizosphere of Sophora tomentosa were collected. From the soil samples, trap cultures with this species were established to extract spores and to evaluate arbuscular mycorhizal fungi colonization in legume roots, as well as to capture rhizobia. Rhizobia strains were isolated from nodules collected in the field or from the trap cultures. Representative isolates of the groups obtained in the similarity dendrogram, based on phenotypic characteristics, had their 16S rRNA genes sequenced. The legume species showed nodules with indeterminate growth, and reddish color, distributed throughout the root. Fifty-one strains of these nodules were isolated, of which 21 were classified in the genus Bacillus, Brevibacillus, Paenibacillus, Rhizobium and especially Sinorhizobium. Strains closely related to Sinorhizobium adhaerens were the predominant bacteria in nodules. The other genera found, with the exception of Rhizobium, are probably endophytic bacteria in the nodules. Arbuscular mycorrhizal fungi was observed colonizing the roots, but arbuscular mycorhizal fungi spores were not found in the trap cultures. Therefore Sophora tomentosa is associated with both arbuscular mycorhizal fungi and nodulating nitrogen-fixing bacteria.